21st Century Skills-Based Beginner Level Reading Teaching Materials: A Need Analysis Result - Frida Philiyanti; Cut Erra Rismorlita (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
This study aims to determine the needs of beginner-level reading teaching materials in Japanese Language Education Department of UNJ based on the demands of 21st century skills. This is important to do considering reading teaching materials that currently used are focused on achieving language competency-based learning only. Along with technological developments, especially during the current pandemic, requires researchers in the field of language education to take part in developing other skills outside of language itself. There are four skills that must be mastered by a learner facing the 21st century, known as 4Cs, namely Creativity, Critical Thinking, Communication, and Collaboration (Bialik, Trilling, & Groff, 2015). In order to achieve these goals, various learning components are required, such as instructional methods, teaching materials, and so on. This study focuses on the development of beginner-level Japanese reading materials that can support building these four skills. This need analysis research is conducted as the initial step of the development research method in determining information about the needs of beginner-level reading teaching materials that support the fulfillment of 21st century skill demands. The data collection technique was conducted by distributing questionnaires to 100 respondents and interviewing analyzing currently used reading material. The results of the questionnaire survey show that 94.75% of respondents need teaching materials that be able to train 21st century skills especially the metacognitive skill, critical thinking, and digital literacy. Moreover, 91% of respondents need contextual learning process that emphasize the process of inquiry and self-reflection. And from the reading material analysis, it is known that the current teaching materials are focused on basic literacy skills only.